A double auction mechanism for coordinating lot-sizing in supply chains. Issue 7 (12th July 2021) - Albrecht, Martin
Abstract: This paper presents an auction mechanism for the coordination of dynamic, uncapacitated lot-sizing problems in two-party supply chains where parties' local data are private information and no external mediator is involved. In the first stage of the mechanism, the buyer generates supply proposals which potentially lead to system-wide improvements, and communicates them to the supplier. Then both parties evaluate the cost impact of the different proposals for their local planning domains. In the second stage, buyer and supplier submit sealed bids on each proposal. Then the bids are opened and the proposal with the greatest surplus is implemented. The procedure for proposal generation is efficient and scalable. It identifies the system-wide optimum in special cases, finds close-to-optimal solutions for general settings in computational tests, while the number of needed proposals increases linearly with the number of time periods and items supplied. Further analytical and numerical analyses indicate that the auction in the second stage is highly efficient.